The halo fixator - Bono, Christopher M (Journal of the American Academy of Orthopaedic Surgeons, 2007)
The halo fixator may be used for the definitive treatment of cervical spine trauma, preoperative reduction in the patient with spinal deformity, and adjunctive postoperative stabilization following cervical spine surgery. Halo fixation decreases cervical motion by 30% to 96%. Absolute contraindications include cranial fracture, infection, and severe soft-tissue injury at the proposed pin sites. Relative contraindications include severe chest trauma, obesity, advanced age, and a barrel-shaped chest. In children, a computed tomography scan of the head should be obtained before pin placement to determine cranial bone thickness. Complications of halo fixation include pin loosening, pin site infection, and skin breakdown. A concerning rate of life-threatening complications, such as respiratory distress, has been reported in elderly patients. Despite a paucity of contemporary data, recent retrospective studies have demonstrated acceptable results for halo fixation in managing some upper and lower cervical spine injuries.